Mechanical and thermal properties of composite board prepared by using polypropylene and cardboard with addition of Maleic Anhydride (MA) as coupling agent: article - Zuri, Nurul Fatihah; Mulana, Farid (2019)
Worldwide issues about solid paper waste are very typical these days. There is disposed of solid paper waste has reached 67 million tons that wound up in landfill. The solid paper waste such as cardboard will be mix with propylene to enhance the strength between the two component and with addition of MA (maleic anhydride) as the coupling agent to enhance the strength of composite board. The experiment started with the number of ratio of polypropylene as the matrix while cardboard as filler. The ratio starts with none of coupling agent present which are 40:60, 60:40, 50:50 and 75:25. The experiment continues with different ratio of matrix: filler: coupling agent. They are 40:50:10, 50:40:10, 60:30:10 and 75:15:10. The testing and analysis is includes tensile and bending testing. The research is about to indicate the effectiveness of the coupling agent that will be use and the suitable ratio of matrix and the filler with amount of the compatibilizer that will produce a good composite board. The result showed that there are increased of the bond within the polymer and cardboard resulted from mechanical testing and thermal analysis